Internal Climate Variability in the Present Climate and the Change in ENSO Amplitude in Future Climate Simulations - Hyun, Seung-Hwon; Yeh, Sang-Wook; Kirtman, Ben P.; An, Soon-Il (Frontiers in Climate, 2022)
In this study, we define a metric for the intensity of internal climate variability (ICV) based on global surface temperature in the present climate and suggest that it can be used to understand the diversity of projected changes in ENSO amplitude in the future. We analyze both the 35-member Community Earth System Model Large Ensemble and the 30-members from Geophysical Fluid Dynamical Laboratory Large Ensemble from the present climate to future climate. While ENSO amplitude tends to decrease from the present climate to the end of 21st century in some ensemble member with a strong ICV during the present climate, it increases or stays the same in other ensemble members with a weak ICV. The result indicates that the intensity of ICV in the present climate in climate models may cause the difference of ENSO amplitude changes in a warmer world. Therefore, the intensity of ICV in the present climate should be cautiously examined in climate models to correctly project the ENSO amplitude changes in a changing climate.